EMERGENCE OF WOMEN EMPOWERMENT THROUGH INCLUSIVE DEMOCRACY IN PAKISTAN (Proceedings of the International Conference on Future of Women, 2018)
Empowerment is "the result of the process which enables an individual to know about herself / himself, what she/he wants, express it, try to get it and fulfill their needs, enhance confidence, awareness, mobility, choices, control over resources and decision making power. The phenomenon of empowering someone implicitly comments on the powerlessness of the individual before. Empowerment is an active multidimensional process which should enable women to realize their identity and powers in all spheres of life, including greater autonomy in decision making as well as participation in all political activities”. Politics being center of power is dominated by males in all over the world including Pakistan. The share of Women is nearly half of the population but still patriarchal society creates hurdles in their way of empowerment. Although all three constitution of Pakistan demonstrated for 5% quota of reserved seats for women in the Legislative Assembly, however, the demand for higher representation was always there. So due to this persistent demand of higher representation, the reserved quota was raised to 33% seats for women in legislative councils at the local, tehsil, municipality and district level and at the National and Provincial level it was enhanced to 17% making it highest representation in the world. In my article, I will unleash the struggle for women political representation and its impacts upon society.
Keywords: Women; empowerment; democracy; constitution